2011
DOI: 10.4100/jhse.2011.62.15
|View full text |Cite
|
Sign up to set email alerts
|

Technical skill differences in stroke propulsion between high level athletes in triathlon and top level swimmers

Abstract: Bottoni A, Lanotte N, Boatto P, Bifaretti S, Bonifazi M. Technical skill differences in stroke propulsion between high level athletes in triathlon and top level swimmers. J. Hum. Sport Exerc. Vol. 6, No. 2, pp. 351-362, 2011. In the latest decades the arm propulsion mechanism in human swimming has been an issue of great interest for researchers. The availability of new devices which can easily measure the stroke propulsion by means of a non invasive gauge allows the study of technical skills in real swimming, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Posture and dynamic body activities of athletes have been monitored using MEMS-based sensors. The body positioning of swimmers at different stages was visualized using MEMS-based pressure sensors (Bottoni et al , 2011). MEMS-based shape sensors are earmarked for their application and can perform in workplaces where strain and optoelectronic sensors cannot be installed.…”
Section: Review Of Shape Sensing Methods and Fiber Optics Based Shape Sensingmentioning
confidence: 99%
“…Posture and dynamic body activities of athletes have been monitored using MEMS-based sensors. The body positioning of swimmers at different stages was visualized using MEMS-based pressure sensors (Bottoni et al , 2011). MEMS-based shape sensors are earmarked for their application and can perform in workplaces where strain and optoelectronic sensors cannot be installed.…”
Section: Review Of Shape Sensing Methods and Fiber Optics Based Shape Sensingmentioning
confidence: 99%
“…Human activity recognition measured by IMUs is applied to several fields of medicine [20,21], rehabilitation [22], robotics for exoskeleton-based patient training [23,24] and sport [25]. Concerning this last field in further detail, applications involve tennis [26], football [27,28], swimming [29][30][31][32][33], basketball [34], cycling [35], skiing [8,9], martial arts [36] and running [37]. Interactive solutions have been introduced [30] which are able to represent in real time the 3D spatial positioning of the body in sport activities in order to evaluate the posture and kinematics of athletes.…”
Section: Inertial Sensorsmentioning
confidence: 99%
“…Another interesting solution was proposed by Bottoni et al , who used wearable mini paddles provided with MEMS pressure sensors to monitor technical skill differences in swimmers. The authors found that each athlete showed a distinctive shape of the pressure curve, but triathlon swimmers showed a greater variability in the pressure pattern than top level swimmers [ 105 ]. Pressure sensors were also recently mounted on the shoulders of front row rugby players, to measure the mechanical loads on professional players of 11 elite rugby teams, when they adopted different strategies during scrummaging.…”
Section: Mems-based Sensor Technologies For Human Centred Applicatmentioning
confidence: 99%